Does microneedling with 5% minoxidil offer added advantage for treatment of androgenetic alopecia in comparison to use of topical 5% minoxidil alone? - Malhotra, Karan; Herakal, Kallappa C. (International Journal of Research in Medical Sciences, 2020)
Background: Androgenetic alopecia is the most common cause of chronic hair loss. The FDA approved treatment for male androgenetic alopecia are Finasteride and Minoxidil. But many patients do not respond to these medications. Microneedling is a recent modality that releases several growth factors and enhances penetration of minoxidil, thereby promoting hair growth. Methods: 60 patients, aged 21-40 years, with androgenetic alopecia were divided into 2 groups. In group A, patients were subjected to microneedling twice monthly, immediately followed by application of topical 5% minoxidil solution over the scalp and then 1 ml twice daily. In group B, patients were treated with application of 1ml of topical 5% minoxidil solution over the scalp twice daily. The results were evaluated based on patient’s and physician’s assessment based on the standardized 7-point evaluation scale. Results: Patients in group A showed statistically significant improvement (p value<0.05) compared to group B. Headache and erythema were the most common side effects encountered in both the groups. Conclusions: Microneedling with 5% minoxidil is a safe, simple and cost-effective modality and is a promising treatment option for patients with androgenetic alopecia. It showed much better results when compared to use of topical 5% minoxidil solution alone.